Mendeteksi Tepi Citra Penyakit Hemokromatosis Dengan Menggunakan Metode Log (Laplacian Of Gaussian) - Resdiana Hutagalung (Yayasan Kita Menulis, 2020)
Hemochromatosis is a genetic or hereditary disease. Abnormalities of iron metabolism characterized by excessive deposition of iron in the tissues. Derivative conditions that cause the body to absorb too much iron from the food eaten. Excess iron is stored in organs such as the liver, heart and pancreas. Excess iron can cause toxicity to these organs, and is life threatening because it can cause diseases such as cancer, cardiac arrhythmias, and cirrhosis. LOG method (Laplacian of Gaussian) is a second-order edge detection operator or has a derivative filter whose function can detect areas that have rapid changes (rapit change) such as edges (edges) in the image. But this laplacian is very sensitive or low to the presence of noise. For that, the image will be smoothed first by using Gaussian. Thus a new derivative function is known, namely LoG or Laplacian of Gaussian. Many methods are used in solving edge detection problems, including Prewitt Operators, Sobel Operators, Canny Operators, but among all these methods, the Laplacian of Gaussian method is the method most often used in detecting edges. For this reason, it is hoped that the LoG (Laplacian of Gaussian) method can help to detect hemochromatosis. Can help how severe the disease has developed, and what symptoms can later be caused, so that it can help in the healing process.